Factors Related to Care Managers’ Experiences of Making Proxy Decisions about Older Adults Living Alone: A Cross-Sectional Study - Hisao Nakai; Kuniko Ishii; Takako Sagino (Nursing Reports, 2023)
In Japan, the number of older adults living alone who require nursing care continues to rise. The purpose of this study was to identify factors associated with care managers’ experiences of making proxy decisions about life directions for older adults who live alone and whose intentions cannot be fully confirmed. The participants were care managers of in-home long-term care support providers nationwide. An original self-report questionnaire was created with reference to previous research and a web-based survey was conducted. The responses were obtained from 241 people and 211 people were included in the analysis. Two factors were identified that were related to care managers’ experiences of proxy decision-making about the life direction of older adults living alone whose intentions could not be fully confirmed: the ability to perform administrative tasks (odds ratio [OR] 3.38, 95% confidence interval [CI]: 1.39–8.22) and the observed cognitive deterioration (OR 2.89, 95% CI: 1.06–7.83). Even if older adults living alone can independently perform administrative tasks, observed cognitive deterioration may be a prodromal sign that such adults will be unable to make decisions about their future life.